Corneal thickness changes in myopic children during and after short‐term orthokeratology lens wear. (20th April 2021) - Wan, Kin; Yau, Hing Tuen; Cheung, Sin Wan; Cho, Pauline
Abstract: Purpose: To evaluate thickness changes in the central and mid‐peripheral cornea (CCT and mPCT), corneal epithelium (CET and mPET) and stroma (CST and mPST) of myopic children during and after short‐term orthokeratology (ortho‐k) lens wear, with conventional (CCF, 0.75 D) and increased compression factors (ICF, 1.75 D). Methods: This was a self‐controlled case series study. Subjects wore a CCF lens in one eye and an ICF lens in the other. Anterior segment optical coherence tomography images were captured weekly for 1 month during lens wear and for 2 weeks after discontinuing lens wear. CCT and CET (central 3‐mm cornea) and mPCT and mPET (within a 4–6 mm diameter annulus) were measured. Stromal thickness (ST) was determined by subtracting epithelium thickness (ET) from corneal thickness (CT). The repeatability of the analytical software was also investigated on age‐matched spectacle‐wearing subjects ( n  = 98). Results: Excluding three outliers (>3 S.D.s), the coefficient of repeatability and intraclass correlation coefficients of 98 spectacle‐wearing subjects ranged from 2.63 to 4.64 μm and from 0.90 to 0.99, respectively. For the weekly‐change study, CCT and CET in both eyes were significantly thinner after lens wear ( p  < 0.001) and CET thinning in the ICF eyes were significantly higher ( p  < 0.02). CCT changes were mainly contributed by CET. CST, mPCT, mPET and mPST changes were not significant ( p  > 0.20) in either eye. CT (all sublayers) rebounded to baseline values 2 weeks after discontinuing lens wear (0.99 >  p  > 0.12). Conclusions: Significant reductions in CT and ET, but not ST, were observed within 1 month of ortho‐k lens wear. Wearing ICF lenses resulted in a higher reduction in CET. Corneal thickness changes were reversible after discontinuing lens wear.